TOWARDS THE SUSTAINABLE URBAN DEVELOPMENT OF METROPOLITAN CALLAO, PERU, TO 2050 - Castillo-García, Rodolfo Francisco (2020)
This article is the product of academic research, personal refl ections, professional experiences, and technical proposals of the Author about the evolution of the urban planning of Callao in the period 1949 - 2020, and about the sustainable urban development of Metropolitan Callao, Peru, with a view to the year 2050. In that perspective, the objective of this article is to make some refl ections on the evolution of the urban planning of Callao in the period 1949 - 2020. And submit technical proposals to promote the planning of sustainable urban development of Metropolitan Callao, with a view to the Bicentennial of the Independence of Peru (2021), to the 200° Anniversary of the Creation of the Litoral Province of Callao (2036), and the second half of the 21st Century (2050). Keywords: Callao – metropolis – sustainable urban development – urban planning